Adult Learning and the Shrinking Globe - Jay M.A. Parker; Joshua C. Collins (Adult Education Research Conference, 2015)
The purpose of this roundtable is to explore the evolution of Adult Education in several European nations relative to the United States and the advantages of the broadened European vision of adult learning as lifelong-lifewide. Through examining these practices we may discover options for inclusion in the United States.
Keywords: adult education; andragogy; vocational education; Western Europe; globalization.